The Cyanobacterial "Nutraceutical" Phycocyanobilin Inhibits Cysteine Protease Legumain. (26th January 2023) - Wilkinson, Isabel V. L.; Castro‐Falcón, Gabriel; Roda‐Serrat, Maria C.; Purdy, Trevor N.; Straetener, Jan; Brauny, Melanie M.; Maier, Lisa; Brötz‐Oesterhelt, Heike; Christensen, Lars P.; Sieber, Stephan A.; Hughes, Chambers C.
Abstract: The blue biliprotein phycocyanin, produced by photo‐autotrophic cyanobacteria including spirulina ( Arthrospira ) and marketed as a natural food supplement or "nutraceutical, " is reported to have anti‐inflammatory, antioxidant, immunomodulatory, and anticancer activity. These diverse biological activities have been specifically attributed to the phycocyanin chromophore, phycocyanobilin (PCB). However, the mechanism of action of PCB and the molecular targets responsible for the beneficial properties of PCB are not well understood. We have developed a procedure to rapidly cleave the PCB pigment from phycocyanin by ethanolysis and then characterized it as an electrophilic natural product that interacts covalently with thiol nucleophiles but lacks any appreciable cytotoxicity or antibacterial activity against common pathogens and gut microbes. We then designed alkyne‐bearing PCB probes for use in chemical proteomics target deconvolution studies. Target identification and validation revealed the cysteine protease legumain (also known as asparaginyl endopeptidase, AEP) to be a target of PCB. Inhibition of this target may account for PCB's diverse reported biological activities. Abstract : Out of the blue : "Spirulina" is a biomass of Athrospira cyanobacteria that is widely regarded as a "superfood" because of its nutritional properties and various health benefits. Phycocyanobilin, the photosynthetic pigment in spirulina, was demonstrated to inhibit the cysteine protease legumain, which might account for spirulina's capabilities.